PENGGUNAAN MODEL PEMBELAJARAN TUTOR SEBAYA UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPA SISWA KELAS VIII SMP TAMAN DEWASA IBU PAWIYATAN TAHUN AJARAN 2012/2013 - Deni Afriani; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
This research purposes to increase student liveliness and learning outcomes at the eighth grade student through peer teaching at SMP Taman Dewasa Ibu Pawiyatan in academic year 2012/2013. It is because of some learning problems at class VIII A SMP Taman Dewasa Ibu Pawiyatan such as: 1). Teacher face come constraints in applying the concept to student, 2) there is assumption that science is hard because of its formula which is must be remembered, 3) too many material to be learned in school which make student are not interested, 4) they tend to cluster with certain student, 5) students are not active in the class, 6) the low value of student learning outcome in science. This research is an action research that is conducted collaboratively. The subjects of this research are 20 students in class VIII A of SMP Taman Dewasa Ibu Pawiyatan Tamansiswa. The object of this research is learning through peer teaching, liveliness, and students learning outcomes. The data collecting technique is conducted by observation, interview, documentation and test. Data analysis technique of observation sheet or questionnaire are conducted by calculating the total value of each indicator and learning outcome test is conducted by searching the median of test and counting the percentage that fulfill the passing grade.The reasult shows that after applying peer teaching in class VIII A of SMP Taman Dewasa Ibu Pawiyatan Tamansiswa, the liveliness and learning outcomes of science subject go up. It is proven by the enhancement of average percentage of student liveliness observation worksheet for each cycle; the average of liveliness indicator in cycle 1 is 69,875%. It increases 8,9575% to 78,8325% in cycle 2. The average learning outcomes of science in pre-action is 55,7 increase to 65,7 in cycle 1 and 76,3 in cycle 2. The numbers of student that pass the passing grade in the pre-action are 5 students with a percentage of 25%. In cycle 1, it increases to 60% with 12 students passing the passing grade and it becomes 70% in cycle 2 with 14 students. Based on the result of research conducted, the researcher advices science teacher to apply peer teaching as a variation of the learning model.